Clinical forum. Investigating the engagement and learning of students with learning disabilities in guided inquiry science teaching. - Palincsar AS; Collins KM; Marano NL; Magnusson SJ (Language, Speech & Hearing Services in Schools, 2000)
Contemporary reform efforts pose numerous challenges for students and their teachers, especially in the context of inclusion classrooms that serve students with diverse academic and social profiles. The research reported in this article was conducted for the purpose of closely studying the engagement and learning of students who have learning disabilities as they participate in a particular approach to guided inquiry called Guided Inquiry supporting Multiple Literacies (GIsML). Questions guiding the research included (a) What are the opportunities and challenges that GIsML instruction presents students with special needs? (b) How do students with special needs respond to these opportunities and challenges? and (c) What hypotheses emerge from the data that will usefully guide subsequent research investigating the means of mediating these students' participation in GIsML for the purpose of enhancing their engagement and learning? The research was conducted using an array of ethnographic methods. The findings were summarized in a set of claims concerning the engagement and learning of these students. Finally, cases of individual students were constructed to illustrate these claims. The article concludes with the case of one fourth-grade student as he engaged in a program of study investigating why objects float and sink. The case revealed (a) the ways in which, in the context of guided inquiry, the student achieved a number of positive outcomes; (b) how his learning problems, principally with regard to print literacy, revealed themselves in his activity; and (c) how contextual features served to enhance and deter his engagement and learning, as well as the engagement and learning of others.